Analisis Pengaruh Kepuasan Atas Pelayanan Dokter Terhadap Minat Kunjungan Ulang (Studi Pada Pasien Umum Di Instalasi Rawat Jalan RSUD A Dadi Tjokrodipo Bandar Lampung) - Nita Sahara (Jurnal Ilmu Kedokteran dan Kesehatan, 2019)
Background: a number of patient with personal payment was only 10% of overall visitation in 2014. Pre survey of 33 respondents in Rsud A Dadi Tjokrodipo Bandar Lampung in may 2015, showed that 60% of patients did not interest to re-visit and 65% of them were not satisfied with the doctor services. The aim of this research was to obtain the influence of satisfaction with doctor services to revisit interest in ambulatory care of Rsud A Dadi Tjokrodipo Bandar Lampung 2015.Methods: quantitative analytic with cross sectional approach. The study was conducted at the ambulatory care patients. Sample of the research was 178 people taken by using accidental sampling based on the inclusion and exclusion criteria. The data analysed with univariate, bivariate by chi square test, and multivariate by logistic regression test.Results: the percentage of patients most satisfied with the technical medical doctors (57.9%), attitude of doctors (54.5%), the delivery of information by doctor (51.7%), timeliness of care doctor (52.8%), and availability time consulting doctor (55.1%) and 56.7% interest in visiting again. There were influence from satisfaction for services provided doctor to patient revisit interest in ambulatory care of rsud a dadi tjokrodipo bandar lampung 2015, with variable satisfaction of attitude doctor most influence to patient revisit interest (OR = 2.759). Suggestion: the management called on doctors to cultivate smiles, greetings and arrive on time in providing services and facilitate the training of the doctor-patient personality.